Agarwood Formation in Gyrinops versteegii Seedling Stage using Four Types of Inducers - Wiwin Hidayat; Tri Mulyaningsih; Aida Muspiah (Jurnal Sylva Lestari, 2022)
Agarwood is decayed wood that contains aromatic resins. It is formed biotically by bacterial, fungal, and physical infections due to injuries, such as broken branches, insect and mammal attacks, lightning strikes, and fires. The natural formation of agarwood has encouraged the development of artificially induced agarwood through inducer inoculation. This study aimed to determine the formation of agarwood at the seedling stage, the quality of agarwood produced, and the best inducer to induce agarwood. The research was conducted in March-June 2021 at the Greenhouse of the Faculty of Mathematics and Natural Sciences, Mataram University, Lombok, West Nusa Tenggara. The research method used was a complete randomized design consisting of four inducer treatments such as distilled water (control), liquid inducer, gel inducer, and paste inducer. Each treatment was repeated three times. Twelve experimental units were obtained. Data were analyzed using an analysis of variance, followed by the least significant difference test if the results were significant. The results showed that inoculation of G. versteegii at the seedling level using four inducers could produce agarwood that is classified in kamedangan class. Inoculation using a gel inducer resulted in the highest kamedangan quantity, and the liquid inducer produced the longest transmission of 10.83 cm and the best kamedangan quality. Keywords: agarwood, Gyrinops versteegii, inoculation, Lombok, seedling